CRIMINAL LIABILITY FOR FAILURE TO EXECUTE COURT DOCUMENTS: SOCIAL NECESSITY, LEGAL DEVELOPMENT AND PRACTICAL PROBLEMS (World Conference on Social Sciences, Law and Public Policy, 2026)
This thesis analyzes the socio-legal foundations of criminal liability for failure to execute judicial documents, its impact on the effectiveness of justice, and the stages of historical development of criminal legislation. It also critically examines the changes in Articles 232 and 232¹ of the Criminal Code of the Republic of Uzbekistan, the relationship between administrative and criminal liability, and the significance of reforms in the field of execution of judicial documents.
Keywords: justice, judicial documents, execution, criminal liability, judicial power, judicial execution, criminal law, execution proceedings.